A STUDY ON IMPACT OF AGILE AND DEVOPS PRACTICES ON SOFTWARE PROJECT MANAGEMENT SUCCESS - Maharao, Calvina Suhas (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This paper explores the impact of Agile and DevOps practices on software project management, focusing on their integration into the software development lifecycle (SDLC). Agile and DevOps are modern methodologies that aim to improve flexibility, collaboration, and continuous delivery in software development. By examining their influence on project management practices, this study provides insights into how these methodologies enhance or disrupt traditional management approaches, particularly in terms of productivity, communication, and project success. It also discusses the benefits and challenges faced by organizations adopting these practices, alongside their synergistic effect when implemented together. The research aims to provide a comprehensive understanding of the role of Agile and DevOps in transforming software project management.